Relasi Islam dan Negara di Indonesia Perspektif Fiqh Siyasah dalam Pemikiran Politik Nurcholish Madjid - Yumnah, Siti (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
: The relationship between Islam and the State becomes an actual and dynamic discourse in every phase of the development of civilization both in the Western and Eastern world. The debate revolves around the question of the form of the state, whether it is integral, symbiotic or secular. The relationship between Islam and the state is still being discussed through the media and discussions of Muslim intellectuals, one of them is Nurcholish Madjid, one of the Islamic political thinkers in Indonesia and many intellectuals who bring up ideas with nationalist insights. One of them is his thoughts on the relationship between Islam and the State in Indonesia. This thought, although quite controversial when first raised but has a major influence on national and Islamic discourse in Indonesia. Fiqh Siyasah's view of Nurcholish Madjid's thoughts is included in the study of siyasah dusturiyah. Although in Islam it never determines the particular form and pattern of a country that must be practiced by Muslims, but establishing a State is an obligation of Muslims. The state is a tool for Muslims to be able to implement the teachings of Islam, so that the goal of syara' creates benefit and rejects harm can be achieved in society